DEVELOPING INTERCULTURAL COMPETENCE THROUGN ENGLISH LANGUAGE TEACHING - Abdumajidova Sabrin Baxtiyor qizi (International Journal of Literature and Language Studies, 2026)
This article discusses the importance of developing intercultural competence through English language teaching in modern educational contexts. The study explains the relationship between language and culture and emphasizes the necessity of integrating cultural awareness into all language skills. In addition, the article analyzes various teaching strategies and classroom activities that promote intercultural communication, tolerance, empathy, and global understanding among learners. The research also highlights the role of teachers in preparing students for effective communication in multicultural environments. The findings demonstrate that intercultural competence is an essential component of successful English language education in the twenty-first century.